Prevention of acute radiation-induced Proctitis by Aloe vera: a prospective randomized, double-blind, placebo controlled clinical trial in Pelvic Cancer patients - Adeleh Sahebnasagh; Arash Ghasemi; Jafar Akbari; Abbas Alipour; Hossein Lashkardoost; Shahram Ala; Seyed Jalal Hosseinimehr; Ebrahim Salehifar (BMC, 2020)
Abstract Background Acute radiation-induced proctitis (ARP) is the most common side effect following radiotherapy for malignant pelvic disease. This study evaluated the efficacy of Aloe vera ointment in prevention of ARP. Methods Forty-two patients receiving external-beam radiotherapy (RT) for pelvic malignancies were randomized to receive either Aloe vera 3% or placebo topical ointment during radiotherapy for 6 weeks. These patients were evaluated based on the severity (grade 0-4) of the following symptoms weekly: rectal bleeding, abdominal/rectal pain, diarrhea, or fecal urgency. RTOG acute toxicity criteria and psychosocial status of the patients were also recorded weekly. Lifestyle impact of the symptoms, and quantitative measurement of C-reactive protein (CRP), an indicator of systemic inflammation, were also measured. Results The results of present study demonstrated a significant preventive effect for Aloe vera in occurrence of symptom index for diarrhea (p < 0.001), rectal bleeding (p < 0.001), and fecal urgency (p = 0.001). The median lifestyle score improved significantly with Aloe vera during RT (p < 0.001). Intervention patients had a significant lower burden of systemic inflammation as the values for quantitative CRP decreased significantly over 6 weeks of follow-up (p = 0.009). Conclusion This study showed that Aloe vera topical ointment was effective in prevention of symptoms of ARP in patients undergoing RT for pelvic cancers. Trial registration IRCT201606042027N6 . Registration date: 2016-09-04.